2017
DOI: 10.24170/7-1-1962
|View full text |Cite
|
Sign up to set email alerts
|

Audit of paediatric cardiac services in South Africa

Abstract: confirmation of congenital heart lesions in the foetus, the care of children with acquired heart disease and the investigation of innocent murmurs of childhood. There is a local perception that the demand for these services far exceeds the available skills in South Africa. In addition to the cardiological needs of our population, the need for surgery for children with heart lesions appears

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 3 publications
1
13
1
Order By: Relevance
“…This screening practice would unnecessarily increase the workload on already over-extended and understaffed healthcare services, and would furthermore limit the number of children who could be accommodated for developmental screening. (17,22) Referral for developmental screening in the current study was far lower than the 90% of practitioners in the US survey who reported regularly referring children for developmental screening. US practitioners also referred more children aged two years and older for developmental screening.…”
Section: Children With Chdcontrasting
confidence: 66%
See 1 more Smart Citation
“…This screening practice would unnecessarily increase the workload on already over-extended and understaffed healthcare services, and would furthermore limit the number of children who could be accommodated for developmental screening. (17,22) Referral for developmental screening in the current study was far lower than the 90% of practitioners in the US survey who reported regularly referring children for developmental screening. US practitioners also referred more children aged two years and older for developmental screening.…”
Section: Children With Chdcontrasting
confidence: 66%
“…The shortage of paediatric cardiologists in the country makes it highly probable that many children with CHD are cared for by general paediatricians. (16,17) The poor response from general paediatricians (36.8%) may indicate that they are either not treating children with CHD and/or that they are unaware of the developmental risks faced by these children.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, only 26% of the approximately 114 children with simple transposition of the great arteries born annually are diagnosed and receive life-saving corrective surgery. (22,23) The arterial switch operation for neonatal correction of transposition of the great arteries was introduced in South Africa in 1988. We estimate that approximately 1 100 children have undergone this procedure in our country.…”
Section: Discussionmentioning
confidence: 99%
“…(7,15) A recent audit of paediatric cardiac services revealed that only 25% of children in South Africa with CHD received the care that they needed from public health services. (16) These same authors subsequently reported that there is an accumulated backlog of untreated CHD and every year over 3 000 children either die, or become disabled, from their specific congenital heart condition. (6) The Medical Research Council of South Africa's statistics revealed that cardiac abnormalities accounted for 1.2% of under 5 mortality.…”
Section: Introductionmentioning
confidence: 99%